Coping Behavior: Personality Invariants of Professional Stress in Legal Activity - Martirosian, Marina (Psychological Prospects Journal, 2018)
The theoretical grounding of the relationships regularities of personality invariants of professional stress experience in legal activity by means of developing appropriate coping behavior of these specialists has been presented in the article. The theoretical model of personality invariant precondition of coping-behavior of professional stress experience in legal activity has been developed; the main functional characteristics of coping behavior of a personality (minimization of negative effects of circumstances, adaptation, support of positive «Image of Self», support of emotional balance, support of interaction with other people) have been singled out; the characteristics of professional stress experience in legal activity in the features of professional responsibility and contradiction have been indicated. It has been emphasized, that overcoming of unfavorable professional situations depends on individual peculiarities of a personality, which are formed in the complex of personality qualities of specialists (moral, psychological, communicative, emotional, volitional, cognitive and intellectual), which provide the psychological potential and implementation efficiency of complex professional tasks of a jurist. The interrelation of personality invariants in the choice of forms of stressful situations overcoming through the characteristics of professional and psychological readiness (mobilization, orientation, operational, volitional, evaluative) has been determined and the constituents of professional stability through the dominants of a specialists activity (the dominants of cognition and self-cognition, the dominant of activity, the dominant of interaction) have been singled out. The data concerning personality invariant precondition of professional stress regulation in specific modes of psychological coping (rational and emotional) have been presented and analyzed. The influence of negative professional factors in legal activity on the personality status of a specialist and its adaptive abilities in professional stresses overcoming has been revealed.